Systematic Journal Review: A Study of Workplace Incivility in Indonesia - Gustiawan, Deni; Azzahra, Reynia Shifa (International Journal of Social Science and Community Service, 2025)
This paper examines the impact of workplace incivility on employee job satisfaction and commitment in Indonesian organizations. This study uses a Systematic Journal Review (SJR) design with a descriptive qualitative approach to integrate and analyze findings from various scientific articles related to the relationship between workplace incivility, job satisfaction, and employee commitment in Indonesia, with data collected through literature searches from trusted databases and analyzed thematically. The results of the study indicate that workplace incivility has a negative impact on employee job satisfaction and commitment. Behaviors such as insults, discrimination, and unfair treatment can reduce productivity, increase stress, and reduce employee well-being. To address these issues, an inclusive approach and support from responsive leadership are essential in creating a healthy and productive work environment.